Verbraucherrechtsdurchsetzung - Fries, Martin (Mohr Siebeck, 2020)
The value of civil rights depends crucially on their enforceability. Especially when it comes to small claims like consumer claims, enforcement can however prove to be difficult. Martin Fries develops criteria for dispute systems aimed at effectively enforcing consumer rights. His analysis contributes to the recent debate on consumer access to justice.
Description based on print version record.
KU Open Services
Keywords: Law / Jurisprudence; Law; Electronic books